Nilai Sosial Dalam Novel Seporsi Mie Ayam Sebelum Mati Karya Brian Khrisna (Filsafat Prof. Dr. Notonegoro) - Tiara Mulidiya; Maizar Karim; Dimas Anugrah Adiyadmo (STKIP Subang, 2026)
This study aims to identify and describe the social values ​​contained in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna based on the philosophy of values ​​of Prof. Dr. Notonegoro. This study uses a qualitative descriptive approach. The research data are in the form of quotations of sentences, paragraphs, and dialogues contained in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna published by PT Gramedia Widiasarana Indonesia in 2025. Data collection techniques are carried out through reading, listening, and taking notes, while data analysis is carried out by identifying, classifying, and interpreting the social values ​​found in the novel. The validity of the data is tested through expert triangulation. The results of the study show that this novel contains three types of social values ​​according to Notonegoro, namely material values, vital values, and spiritual values. Material values ​​are found in 27 quotations related to the fulfillment of human physical needs. Vital values ​​are found in 45 quotations related to the means or tools that support human activities. Meanwhile, spiritual values ​​were the most dominant, with 157 quotations, consisting of truth (35), beauty (32), moral values ​​(71), and religious values ​​(19). This finding indicates that the novel not only depicts realistic social life but also emphasizes moral and spiritual values ​​that can serve as reflections for readers in understanding the meaning of life.